Pemanfaatan Jaringan Nirkabel Untuk Komunikasi Data dan Suara di SMK Teknik Komputer dan Jaringan di Palembang - Reza Firsandaya Malik; Deris Stiawan; Erwin Erwin; Rossi Passarella; Sutarno Sutarno; Ahmad Fali Oklilas; Ahmad Heryanto (Annual Research Seminar (ARS), 2015)
According to the Basic Data of Directorate of Technical and Vocational Education that there are 18 vocational Computer Engineering and Networks in Palembang with consist of 2 state and 16 private schools. Utilization of the wireless network delivered in the training method that involves cognitive, affective and psychomotor aspects. The basic training taught basic computer network, especially related to wireless networks. These three aspects are evaluated through a pre test and post test. The results of pre and post test showed that 6.7% of the participants were not able to increase their knowledge about the wireless network while 93.3% are able.